A technology commercialization plan of the Amphitrike (Amphibious Tricycle) - Uy, Yunissan Carmel Q.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2014)
Despite the recent calamities the country has faced, the automotive sector remains strong with continuous sales increase for the past years. However, the Philippine transport industry has been engaging in mere importation of commercialized vehicles from its neighbouring countries. This resulted into decreasing innovation capability by the automotive assemblers and productivity lags in the manufacturing sector. Even with brightest Filipino inventors, indigenous automotive brands are still lacking in the country because of its incompetence in terms of technology commercialization. This project report presents a comprehensive and robust commercializaton plan for an amphibious vehicle, called the Amphitrike. The main objectives of this paper are : [1] to identify an appropriate pre-commercialization decision, whether to license, sell or build the Amphitrike; [2] to recognize market opportunities; [3] to develop a technology transfer plan based from the decision made; and [4] to identify the critical points in the process of technology diffusion. The main content of this report is shown on the methodology section, which is divided into five integrated frameworks : [1] what to sell decision strategy; [2] opportunity recognition; [3] crossing the chasm strategy; [4] technology transfer plan; and [5] marketing plan that will be used during the time when the business is launched. What to Sell Decision method is applied into the subject company which is the H2O Technologies, Inc., an R&D company who invented the concept of the Amphitrike. The decision derived from the factors and attributes presented was to sell the technology to a competent organization capable of building the whole product solution. Opportunity has been recognized thru the business concept development where the Amphitrike is described as a three-wheeled vehicle called the H2O Salamander. The Amphitrike's target customers are individuals, groups or organizations who need versatile transport in land and water. It will be distributed via local dealership in the country. Moreover, commercializing a technology is not stimulated with an actual transfer of the idea to prospective developer. A technology transfer plan is also presented in augmenting a robust and comprehensive technology commercialization plan. This section covers several factors in transferring the technology such as certain documents about the technology, intellectual property filed, licensing agreements, and IP valuation. The IP valuation in this paper tells that the Amphitrike, upon bringing ito to the market, will generate substantial revenues for fifteen years. After determining the value of money from the Amphitrike's technology, an action plan shall be prepared on the actual technology transfer. This action plan involves gathering of necessary requirements which involve various costs in manufacturing and distribution. It also covers the timeline before presenting it to prospective investors. Since the Amphitrike is a new product to enter the market, the adoption by its target customers is crucial. This section covers substantial principles from (Rogers 2010) about the categories of technology adopters and their characteristics. Technology adopters are classified into five : [1] innovators, [2] early adopters, [3] early majority, [4] late majority, and [5] the laggards. The degree of differences among these adopters embodies the level of willingness to which they will adopt a technology. The early market category consists of the innovators and early adopters; while, the main stream market consists of the early majority, late majority and laggards. According to (Mohr, Sengupta and Slater 2010), crossing a chasm means getting off the gap between the early market and the mainstream market. This report presented three (3) different approaches in crossing the chasm : establishing a beach head, offering the whole product solution, and integrating factors affecting adoption of innovation strategy. In the case of the Amphitrike, the beachhead entails the public and private organizations with intentional purpose of using the vehicle for flooded rescue operations. The auxiliary applications from the beachhead would result in considerable publicity to reach the mainstream market and make the Amphitrike a viral product. Offering the whole product solution makes it possible to reach the majority thru end-to-end solution in fulfilling the customer's needs. There are six (6) factors that have been presented based from (Moore 2006) that affect the customer's purchase decisions : relative advantage, compatibility, complexity, testability, product benefits, and observability. Integrating these factors serve another strategy in penetrating the mainstream market. A marketing plan was developed after reaching pre-commercialization decision, recognizing business opportunities, planning for technology transfer, and strategizing for technology adoption. This marketing plan serves as a constructive tool upon launching the business. Bringing the Amphitrike to the market requires an analysis of its market demographics. The Amphitrike is a new product in the road transport which intends to disrupt the existing motor vehicles in the country. With the frequent disasters and calamities, floods have become a fatal enemy by most people especially in Metro Manila and nearby provinces. These circumstances have resulted to an inevitable need to adapt and survive. The Amphitrike's versatility in land and flood water provides affected people the capability and comfort of moving from one location to another.
Amphibian vehicles have been around in the 1700s but it didn't commercialize well due to some technical reasons and adaptation constraints. The historical experience of amphibians' attempt to enter the market remains a big challenge. This paper attempts to acquire Amphitrike a position in the automotive industry. It showed, in the recent years, a positive growth on both passenger cars and commercial vehicles. With this, the automotive industry is a potential market for the Amphitrike. Buyer behavior, consumer purchase decisions, customer segments, competition and collaborations are discussed comprehensively on the marketing plan. Moreover, macroeconomic forces are also included in the marketing plan covering its demographics, economic climate, technology and legal and regulatory issues. The target market for the Amphitrike is the Filipino middle class C with average annual income of Php603,000,000. The economic climate spurs positive growth and is believed to continually be strong in the coming years. The technology examined to be of greatest effect to the Amphitrike is the emergence of electric vehicle industry. However, this won't affect the Amphitrike since it can be converted into electric amphibian. Legal and regulatory issues are very much essential to consider in the marketing plan. The Philippine transport industry is regulated by selected government agencies. Compliance on its rules and regulations is needed for the actual use of the Amphitrike. This report targets the First Pacific Limited as the company to acquire the Amphitrike's technology. The company's assets, capabilities, areas of advantage, market position, and strengths and weaknesses are carefully analyzed in the marketing plan. After analyzing the company, financial and non financial objectives are also discussed in the marketing plan. The financial objective for the Amphitrike is to increase its revenue by 20 percent each year and to gain a market share of at least 2 percent in the total passenger car market. Non financial objectives are customer satisfaction, perceived quality and loyalty. Aside from financial and non financial objectives, target market segments and value proposition are also discussed in the marketing plan. The target market of the Amphitrike is the same as that of motorcycle, tricycle and passenger car. Demographics and psychological customer segments are the identified market segments for the Amphitrike. A perceptual map containing multi-level attributes was presented for value proposition. A winning marketing strategy is important to reach to target customers ascertaining awareness with regards to the value and benefit of the Amphitrike. The overall marketing activities planned are paid advertisements, sales promotions, and public relations and publicity. These paid advertisements cover promotions on social media, TV ads, print ads, etc. Sales promotions cover price discounts and rebates offered to early deployment. Public relation and publicity cover sponsorships and partnerships with rescue organizations. The estimated total marketing campaign cost is about Php58,000,000. The price of the Amphitrike ranges from Php250,000.00 to Php350,000.00. Similar financing options used by car dealerships are also applied. Upon the actual marketing campaign and product dealership, several factors on finances and processes for corrective action are also tackled in the marketing plan. Based on the five (5) commercialization frameworks presented, Amphitrike will be a successful innovation if commercialized properly and adapted well by its target customers.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Vehicles; Strategic planning; Urban transportation